Hubungan antara Religiusitas dengan Prestasi Belajar pada Mahasiswa Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung Angkatan 2012 - Rosleny Marliani (Jurnal Psikologi Integratif, 2016)
This research is written  to know the relation between religiosity and academic achievement This research is done by use of correlations research design, by involves 115 respondents. There is statistical testing who will be utilized to test hypothesis that is proposed is `Rank Spearman`. Base acquired statistic result with trusty degree as big as 95% (α = 0, 05) known that correlation coefficient as big as 0,032 by Pv as big as 0,730. It has that mean rejected H1 and H0 accepted, so gets to be said that not available relationship among religious commitment level by academic achievement.